Impact of singular versus combinatorial environmental stress on RONS generation in Drosophila melanogaster larvae - Bomble, Pratibha; Nath, Bimalendu B. (Frontiers in Physiology, 2024)
Cascading effect of temperature, desiccation and nutritional deficiency are climate-change-driven stressors. Literature shows conventional research focusing on one stressor at a time. But in nature, organisms face multiple stressors simultaneously. Our study design comprises investigation of singular and multiple stressors in combinatorial forms using Drosophila as model to fill the knowledge gap in stress-biology research. Oxidative stress should be studied coupled with nitrosative stress to gain an integrated insight of adaptive responses to multiple stress. Our study is the first of its kind described for any insects so far, taking both ROS and RNS (RONS) as endpoints of multiple stress regime which generally converges through oxidative and nitrosative stress. Another hallmark of the present study is the inclusion of mitochondrial enzyme aconitase to evaluate impact of multiple stressors. Inactivation of aconitase enzyme provided an additional biomarker to assess multiple stress. Moreover, this multifaceted study demonstrated fluorescence-based microscopic evidence at the cellular/tissue level for the validation of oxidative and nitrosative stress response. In short, the findings offer new insights into environmental biomonitoring of dominant multiple abiotic stressors impacting non-human biota, namely heat, desiccation and starvation using RONS as stress biomarker in Drosophila model